Effects of a mixture of low doses of atrazine and benzo[a]pyrene on the rat seminiferous epithelium either during or after the establishment of the blood-testis barrier in the rat seminiferous tubule culture model. (February 2020) - Durand, Philippe; Blondet, Antonine; Martin, Guillaume; Carette, Diane; Pointis, Georges; Perrard, Marie-Hélène
Abstract: Atrazine (ATZ), a widely used agricultural pesticide and benzo[ a ]pyrene (BaP), a ubiquitous environmental human carcinogen can induce alterations of spermatogenesis. In the present study, we showed first that our seminiferous tubule culture model, in bicameral chambers, allowed the settlement of the blood-testis barrier (BTB) in 8-day-old male rat cultures and the differentiation of spermatogonia into round spermatids.The effect of a mixture of 1 μg/L of ATZ and 1 μg/L of BaP was then investigated either during or after the establishment of the BTB by using 8- or 20–22-day-old rats. Cultures were performed over a 3-week period. Our results show that claudin-11 and connexin 43 two proteins of the BTB, were impaired by the mixture which also reduced the number of round spermatids (the direct precursors of spermatozoa), by targeting the middle to late pachytene spermatocytes. These effects were observed in 8- and 20–22-day -old rat seminiferous tubule cultures. However, the decrease of the number of round spermatids was faster and more marked in the 8-day- than in the 20–22-day -old rat seminiferous tubule cultures. Our study emphasizes the possible influence of the age of an individual on the effect of (a) toxicant(s) on spermatogenesis. Highlights: Our seminiferous tubule culture allows the settlement of the blood-testis barrier. Effect of a mixture of atrazine and benzo[ a ]pyrene on spermatogenesis. Effect of the mixture during or after the settlement of the blood-testis barrier. The effect was more marked during the settlement of the blood-testis barrier. Our study emphasizes the possible influence of age on the effect of a toxicant.